EVALUATING EFFECT OF BLADES MATERIAL ON ARCHIMEDES SPIRAL HYDRO TURBINES: A COMPARATIVE STUDY FOR SUSTAINABLE HYDROPOWER - Sk Rahad Rahman; Md Mahadi Hassan Parvez; Sultan Mahamud Sheikh; Irfan Ahmed; Md. Abu Daud (Advanced Engineering Letters)
This paper presents a comparative performance analysis of PVC and MS blades in Archimedes Spiral Hydro Turbines (ASHT) for sustainable hydropower generation. There are two types of ASHT prototypes fabricated based on a three-dimensional (3D) design by varying the blade material; one was Poly Vinyl Chloride (PVC) made screw ASHT, and another was Mild Steel (MS) made ASHT. The thickness of PVC and MS was 4 mm and 1 mm, respectively. The generated voltage and current for 0.5 m, 1.0 m, and 1.5 m heads were analyzed, and the output power was compared with various shaft rotations based on the variation of the head. At the same head, voltage and current were obtained much more for MS-made ASHT. At 1.5m, higher voltage and current were investigated; the voltage and current were 10.2V and 0.57A for MS-made. MS-made ASHT exhibited 52.20% and 23.90% more voltage and current, respectively than PVC-made ASHT at 1.5m head. The maximum power was observed for MS-made ASHT, which was 5.82W at 502 rpm. This paper underscores the importance of balancing design parameters, blade material, and operating conditions to optimize ASHT for sustainable hydropower generation.